Estudio de patogenicidad a melon de hongos del suelo causantes de colapso - Beltran, R.=700 1 Armengol, J.; Garcia Jimenez, J.
(En, Es)
Ilus., 30 ref.
Keywords: ACREMONIUM; CUCUMIS MELO; PATOGENICIDAD; HONGOS DEL SUELO; ESPAÑA